2005
DOI: 10.1523/jneurosci.4015-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Inhibition by Catecholamines of Hypocretin/Orexin Neurons

Abstract: Hypothalamic hypocretin enhances arousal, similar to the actions of norepinephrine (NE). The physiological actions of NE were examined in hypocretin neurons identified by selective green fluorescent protein expression in transgenic mouse hypothalamic slices using whole-cell recording. NE induced an outward current, inhibited spike frequency, and hyperpolarized hypocretin neurons dose dependently. Similar actions were evoked by the selective ␣2 adrenergic agonist clonidine. The ␣2 antagonist idazoxan increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
2
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 67 publications
9
80
2
2
Order By: Relevance
“…In contrast, we and Li and van den Pol (2005) observed that mouse orexin neurons showed NAinduced hyperpolarization. To examine whether SD alters the response of mouse orexin neurons to NA, we performed calcium imaging using hypothalamic slices from orexin/YC2.1 transgenic mice in which orexin neurons specifically express calcium-sensing protein.…”
Section: Effect Of Sd On the Na Responsiveness Of Orexin Neuronscontrasting
confidence: 69%
See 2 more Smart Citations
“…In contrast, we and Li and van den Pol (2005) observed that mouse orexin neurons showed NAinduced hyperpolarization. To examine whether SD alters the response of mouse orexin neurons to NA, we performed calcium imaging using hypothalamic slices from orexin/YC2.1 transgenic mice in which orexin neurons specifically express calcium-sensing protein.…”
Section: Effect Of Sd On the Na Responsiveness Of Orexin Neuronscontrasting
confidence: 69%
“…Previous studies have demonstrated that NA (Li et al 2002;Li and van den Pol 2005;Yamanaka et al 2003b) and DA (Yamanaka et al 2003b) show inhibitory effects on orexin neurons. The present study confirms these results, extends these observations to adrenaline and establishes that the hyperpolarization induced by catecholamines involves ␣ 2A -ARs and, subsequently, an activation of GIRK channels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although it was unexpected that the LC and DR did not increase Fos expression in response to SD in VEH-treated animals, the mixed downstream effects of NE and generally inhibitory effects of 5HT on other wakepromoting cell groups (Brown et al, 2012;Li et al, 2002;Li and van den Pol, 2005) contrast with the excitatory effects of Hcrt, HA, and ACh on these groups , suggesting that the LC and DR may be differentially regulated. The elevated Fos expression observed in the LC following forced wakefulness in ZOL but not VEH or ALM treatment groups is also surprising considering the inhibitory effect of ZOL in other regions, but this may be a result of the greatly increased level of stimulation required to keep ZOLtreated rats awake during forced wakefulness coupled with the high sensitivity of Fos expression in the LC to stress (Sved et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…78,79 While orexin activates catecholamines and endocannabinoids, catecholamines and serotonin exert a negative feedback on the orexin system. 80,81 These findings suggest a central role for the orexin systems in the shared biology of feeding and mood disorders.…”
Section: A B C D E F G Hmentioning
confidence: 93%